Professeus D’anglais Natifs et Non-Natifs en FranceNative and Non-native Teachers of English in France (PerCursos, 2006)
L' oposition linguistique entre (natif) et (non-natif) ne peut plus se concevoir comme une oposotiontranchée, mais bienau contraire commeun continu umex primant destrajectoPalabras claves: Politica educacional.Formación de profesores. Educación.O presente artigo apresenta uma análise das políticas educacionais em Cuba com respeito à formação de professores. Para isto, os autores estabelecem as relações que existem entre as categorias política educacional e formação de professores no contexto de educação cubana. A referida análise parte da definição dos conceitos que são relacionados a ambas as categorias e, como resultado, demonstra-se o caráter complementar das referidas relações. Palavras-chave: Política educacional. Formação de professores.Educação.This article presents an analysis of the educational policies in Cuba in regard to the education of teachers. Through this analysis, the authors establish the relations that exist between the categories educational policy and teacher education in the context of Cuban education. That analysis is made by taking the definition of the concepts that are related to both categories as starting points, and as a result, the complementary character of such relations are  demonstrated.Keywords: Educational Policy. Teacher Education. Education.